Survey Perilaku Kesehatan Remaja Siswa SMA Negeri 5 Kota Jambi Tahun 2012 - Dwi Noerjoedianto; Herwansyah . (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2014)
ABSTRACT Background: Nowadays, there are several complex problems of adolescents, including sexuality problems (pregnancy before marriage and abortion), Sexual Transmitted Diseases, HIV and AIDS, as well as drug abuse. The objective of this survey were to perceive behavior, religious adherence, media information, peer group interactions, communication with parents, communication with teachers and community figures, and sexual behavior of adolescents on health behavior. Methods: This survey was an observational survey which used cross-sectional design, and it was equipped with quantitative method. The subjects of survey were between 15-18 years old, 320 students of Senior High School 5 City of Jambi, the samples were only 80 students, and the analysis of data was univariat analysis with research variable. Result: The results show that the most respondents were 16 years old 58 students (72.5%), girls 62 students (77.5%), Islam 72 students (90%) and about 64 students were not active in School Health Unit activities, 72 students (90%) were good at attitude of adolescent reproductive health, 71 students (88.75%) were good at religious activities, 74 students (92.5%) used media to derive piece of information regarding adolescent reproductive health, 58 students (72.5%) had interacted with their friends, about 64 students (80%) sometimes interacted with parents, 46 students (57.5%) occasionally interacted with teachers, 79 students (98.75%) had proper knowledge in terms of sexuality and adolescent reproductive health. Conclusion: In conclusion, almost 90% of respondents had good attitude, and they were good at behavior of adolescent reproductive health. Keywords : Attitude, Behavior, The Adolescent Health, The students of Senior High School